Establishment of the military forces in Great Britain : copybook
British military manual kept by an unknown person. Includes copies of regulations, abstracts, warrants, accounts, computations, and lists of regiments, forces, and officers. Also includes a reference to the 42nd Regiment of Foot "for the defense of the new colony of Georgia and South Carolina" under Col. James Oglethorpe, and an engraved portrait of Oglethorpe.
Collection material in English.
Keywords: Great Britain. -- Army -- Colonial forces -- America; Oglethorpe, James Edward, -- 1696-1785.; Georgia -- History -- Colonial period, ca. 1600-1775.; South Carolina -- History -- Colonial period, ca. 1600-1775.